Horse-rider interaction: A new method based on inertial measurement units - Eckhardt, F.; Witte, K. (Journal of Equine Veterinary Science, 2017)
Highlights: •This study demonstrates the potential of a novel method to determine interaction between horse and rider under field conditions. •Due to recent efforts in sensor technology, it is possible to investigate the kinematics and the interactions of the horse and the rider using small wireless sensors. •Cross-correlation analysis was used to quantitatively evaluate the horse-rider interactions for different gaits and skill levels. •The results indicate significant differences in horse-rider interaction between the different equine gaits. •The factor skill level showed only statistical tendencies.